Implementation of Character Education Before and After The Covid-19 Pandemic: Obstacles, Challenges, and Solution - Sapriya, Sapriya; Supriadi, Acep; Rakhman, Muhammad Arief; Hardiyanti, Retno Ayu; Tanshzil, Sri Wahyuni; Putra, Tarekh Febriana (International Journal Pedagogy of Social Studies, 2022)
Post-pandemic social change requires transformation in every element of education. Transfiguration in the structure of character education is one form of educational transformation. There are various differences and changes in the implementation of character education before and after the Covid-19 pandemic. This article will present a comparison of the implementation of character education during face-to-face learning and distance learning. In the discussion, it will explore the analysis of the obstacles and challenges of character education, then propose a solution idea as a form of character education transformation. . The approach used in this research is a mix method approach with descriptive and literature review analysis. The research subjects were students, teachers, and principals at SMPN 14 Bandung. The findings of this study in conclusions; 1) there are differences in student perceptions of the implementation of character education before and after the Covid-19 pandemic; 2) the habituation-based character education process becomes a promising alternative solution as an effort to transform the character education model.